2021
DOI: 10.1029/2020gl091611
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Atmospheric Fine Particles During the COVID‐19 Pandemic in a Megacity of Eastern China

Abstract: Atmospheric particulate matter (PM) exerts significant impacts on air quality, climate change, and public health (IPCC, 2013; West et al., 2016). The megacities in developing countries, such as China and India, are facing severe air pollution, especially the fine particle (PM 2.5) problem because of their fast-growing economy and urbanization in past decades (Fu & Chen, 2017; Gurjar et al., 2016). To mitigate air pollution, the Chinese State Council implemented the "Air Pollution Prevention and Control Action … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 35 publications
(54 reference statements)
8
29
2
Order By: Relevance
“…The average PM 2.5 concentration was 63 μg m −3 during winter in 2017 in Hangzhou (Table S1), which is lower than the Grade II standard value of 75 μg m −3 . Regional haze events frequently appeared in the YRD in winter because of regional emissions from urban vehicle exhausts and industrial activities (Liu, Zhang, et al, 2020;Xu, Zhang, et al, 2020), as well as the TRT of air pollutants from the NCP (Li, Wang, et al, 2019;Ming et al, 2017). Compared with the NCP, there are no coal-fired heating activities in villages and central heating in urban areas in the YRD during winter.…”
Section: Zhang Et Almentioning
confidence: 99%
“…The average PM 2.5 concentration was 63 μg m −3 during winter in 2017 in Hangzhou (Table S1), which is lower than the Grade II standard value of 75 μg m −3 . Regional haze events frequently appeared in the YRD in winter because of regional emissions from urban vehicle exhausts and industrial activities (Liu, Zhang, et al, 2020;Xu, Zhang, et al, 2020), as well as the TRT of air pollutants from the NCP (Li, Wang, et al, 2019;Ming et al, 2017). Compared with the NCP, there are no coal-fired heating activities in villages and central heating in urban areas in the YRD during winter.…”
Section: Zhang Et Almentioning
confidence: 99%
“…Most current studies have focused on the impact of reduced anthropogenic emissions on aerosols (Fan et al., 2020; Liu et al., 2021; Y. Wang et al., 2020) and the important role played by secondary aerosols in causing air pollution during the lockdown (Huang et al., 2020). Few studies pay attention to the corresponding climatic effects induced by the drastic aerosol change resulting from the anthropogenic emissions reduction during the lockdown (Gettelman et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Their synergistic observation analyses and model simulations showed that anomalously high humidity promoted aerosol heterogeneous chemistry, along with stagnant airflow and uninterrupted emissions from power plants and petrochemical facilities, contributed to severe haze formation. Also, due to nonlinear production chemistry and titration of ozone in winter, both reduced nitrogen oxides that resulted in ozone enhancement in urban areas, further increasing the atmospheric oxidizing capacity and facilitating secondary aerosol formation ( Liu et al, 2021 ;, Huang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%